Efektivitas Maintenance Scheduling Terintegrasi dengan Metode Reliability Centered Maintenance (RCM) di UPT. Industri dan Produk Kayu Disperindag Provinsi Jawa Timur di Kota Pasuruan - Muhammad Syukur; Kafizh Rosyidi (MES Bogor, 2025)
The use of planer machines continues to evolve. Regular maintenance is very important to maintain the reliability of the planer machine, ensuring its function remains optimal. This research combines qualitative and quantitative data. Planer machine maintenance schedule analysis will be carried out in this research using the Reliability Centered Maintenance (RCM) approach. The main objective of this investigation is to assess reliability factors, identify the root cause of failure or damage, and propose a maintenance plan aimed at reducing the occurrence of damage and operational disruptions in various main systems of the planer machine. In industry, especially those in the mechanical engineering field, it is expected to prioritize maintenance scheduling for each machine component, especially critical ones, to prevent damage.